Maternal characteristics associated with gestational weight gain in France: a population-based, nationally representative study. Issue 7 (2nd July 2021) - Amyx, Melissa; Zeitlin, Jennifer; Hermann, Monika; Castetbon, Katia; Blondel, Béatrice; Le Ray, Camille
Abstract : Objectives: To provide nationally representative estimates of gestational weight gain (GWG) and identify maternal characteristics associated with inadequate GWG in France. Design: A population-based study using data from the French National Perinatal Survey: 2010 and 2016. Setting: All maternity units in metropolitan, mainland France (n=535 in 2010; n=493 in 2016). Participants: Singleton live births with GWG data (N=24 850). Primary outcome measures: GWG was calculated as end of pregnancy minus pre-pregnancy weight (kg) and categorised as 'insufficient', 'adequate', or 'excessive' using 2009 Institute of Medicine thresholds. Classification accounted for pre-pregnancy body mass index (BMI) (kg/m 2 ; underweight (<18.5), normal weight (18.5–24.9), overweight (25–29.9), obese (≥30)) and gestational age at birth. We estimated average GWG and the percentage of women in each GWG category. Polytomous logistic regression identified characteristics associated with GWG adequacy. Results: Average GWG was 13.0 kg (SD 5.6), with 26.8% of women gaining insufficiently, 37.0% adequately and 36.1% excessively. Among other factors, insufficient GWG was associated with underweight (vs normal weight; adjusted OR (aOR) 1.4, 95% CI 1.2 to 1.5) and obese (aOR 1.5, 95% CI 1.4 to 1.7) BMI. Excessive GWG was associated with overweight (aOR 2.8, 95% CI 2.6 to 3.1) and obese BMI (aOR 3.3, 95% CI 2.9 to 3.6). Examining obesity classes separately, odds of insufficient GWG increased from obesity class I to III, while odds of excessive GWG decreased from obesity class I to III. Primiparity (insufficient: aOR 0.9, 95% CI 0.9 to 1.0; excessive: aOR 1.2, 95% CI 1.2 to 1.3), maternal characteristics indicative of lower socioeconomic status, and continuing or quitting smoking during pregnancy were also associated with inadequate GWG. Conclusions: In France, insufficient and excessive GWG are common. For optimal outcomes, clinician education, with special attention to the needs of higher risk/vulnerable groups, is needed to ensure all women receive appropriate advice for recommended GWG.